Fluid Shear Stress and Inner Curvature Remodeling of the Embryonic Heart. Choosing the Right Lane!. (2008) - Hierck, Beerend P.; Van der Heiden, Kim; Poelma, Christian; Westerweel, Jerry; Poelmann, Robert E.
Abstract : Cardiovascular development is directed or modulated by genetic and epigenetic factors. The latter include blood flow-related shear stress and blood pressure-related circumferential strain. This review focuses on shear stress and its effects on endothelial cells lining the inner surfaces of the heart and blood vessels. Flow characteristics of the embryonic blood, like velocity, viscosity and periodicity, are taken into account to describe the responses of endothelial cells to shear stress and the sensors for this friction force. The primary cilium, which is an integral part of the shear sensor, connects to the cytoskeletal microtubules and transmits information about the level and direction of blood flow into the endothelial cell. When the heart remodels from a more or less straight into a c-shaped tube the sharp curvature, in combination with the small vessel dimensions and high relative viscosity, directs the highest shear stress to the inner curvature of this pump. This proves to be an important epigenetic modulator of cardiac morphogenesis because when shear stress is experimentally altered inner curvature remodeling is affected which leads to the development of congenital cardiovascular anomalies. The best of both worlds, mechanics and biology, are used here to describe early cardiogenesis.